IMPLEMENTASI MANAJEMEN BERBASIS MADRASAH DALAM UPAYA MENINGKATKAN MUTU SMA BP DARUSSALAM TAHUN PELAJARAN 2023/2024 - Dafit Kurniawan (NURHIDAYAH: Jurnal Ilmu Pendidikan, 2025)
Implementation Madrasah based management contains the meaning of application management in madrasah to improve the quality of education. The main areas in madrasah that can adopt the principles of quality management are: Application of quality management to improve administrative function in managing madrasah; Integrating Madrasah based management in Madrasah curriculum; Using madrasah-based management in the learning process, especially the process of learning in the classroom. The presence of madrasah based management results in a change in conventional management. Improving the quality of education centered on improving the quality of madarsah.